The functional importance of telomere clustering: Global changes in gene expression result from SIR factor dispersion - Taddei, Angela; Van Houwe, Griet; Nagai, Shigeki; Erb, Ionas; van Nimwegen, Erik; Gasser, Susan M. (Genome Research, 2009)
Budding yeast telomeres and cryptic mating-type loci are enriched at the nuclear envelope, forming foci that sequester silent information regulators (SIR factors), much as heterochromatic chromocenters in higher eukaryotes sequester HP1. Here we examine the impact of such subcompartments for regulating transcription genome-wide. We show that the efficiency of subtelomeric reporter gene repression depends not only on the strength of SIR factor recruitment by cis-acting elements, but also on the accumulation of SIRs in such perinuclear foci. To monitor the effects of disrupting this subnuclear compartment, we performed microarray analyses under conditions that eliminate telomere anchoring, while preserving SIR complex integrity. We found 60 genes reproducibly misregulated. Among those with increased expression, 22% were within 20 kb of a telomere, confirming that the nuclear envelope (NE) association of telomeres helps repress natural subtelomeric genes. In contrast, loci that were down-regulated were distributed over all chromosomes. Half of this ectopic repression was SIR complex dependent. We conclude that released SIR factors can promiscuously repress transcription at nontelomeric genes despite the presence of “anti-silencing” mechanisms. Bioinformatic analysis revealed that promoters bearing the PAC (RNA Polymerase A and C promoters) or Abf1 binding consenses are consistently down-regulated by mislocalization of SIR factors. Thus, the normal telomeric sequestration of SIRs both favors subtelomeric repression and prevents promiscuous effects at a distinct subset of promoters. This demonstrates that patterns of gene expression can be regulated by changing the spatial distribution of repetitive DNA sequences that bind repressive factors.